Analysis of the Phenotype and Function of the Subpopulations of Mucosal-Associated Invariant T Cells - Brozova, J; Karlova, I; Novak, J (Scandinavian journal of immunology, 2016)
Mucosal-associated invariant T (MAIT) cells contain two main subpopulations, CD8(+) and double-negative (DN) cells. The first reports suggested that subpopulations of MAIT cells have similar phenotype and function. Recent works, however, demonstrate that the subpopulations have different ontogenesis and are differentially affected by xenobiotic treatment. In this work, we re-examined the possible differences between subpopulations of MAIT cells. We demonstrate that the main subpopulations of MAIT cells (CD8 and DN) are relatively uniform in terms of both phenotype and function. Both populations are memory/activated, tissue-homing and pro-inflammatory. CD8(+) MAIT cells are better equipped for pro-inflammatory functions as they express higher levels of CD16 and NKG2D, produce more pro-inflammatory cytokines (TNF-α and IFN-γ) and have higher cytotoxic potential (contain more granzyme B and express higher levels of CD107A upon stimulation). Our study contributes to the understanding of the heterogeneity of MAIT cell population.
Keywords: mužské pohlaví; interferon gama; receptory IgG; Male; Cell Lineage; imunologická paměť; GPI-vázané proteiny; lektinové receptory NK-buněk - podrodina K; Female; Humans; Immunologic Memory; CD8-pozitivní T-lymfocyty; Lysosomal-Associated Membrane Protein 1; Gene Expression; lidé; MAIT buňky; Middle Aged; ženské pohlaví; lidé středního věku; TNF-alfa; exprese genu; membránový protein 1 asociovaný s lyzozomy; granzymy; GPI-Linked Proteins; buněčný rodokmen; Granzymes; Biomarkers; Immunophenotyping; biologické markery; Mucosal-Associated Invariant T Cells; imunofenotypizace; dospělí; Adult; CD8-Positive T-Lymphocytes; NK Cell Lectin-Like Receptor Subfamily K; Tumor Necrosis Factor-alpha; Interferon-gamma; Receptors, IgG